Web-Enhanced Course Based on Problem-Based Learning (PBL): Development of Interactive Learning Media for Basic Physics II - Diani, Rahma; yuberti, yuberti; Syarlisjiswan, Muhammad Ridho (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
This research aims to develop an active learning media in the form of Web-Enhanced Course. This research and development research follows the development steps of Borg & Gall. Data collection instruments used were validation sheets and questionnaires. The assessments’ average score for the feasibility of the product from the material experts is 84.83%, from media experts is 81.76%, and informatics experts are 83.61% in the very feasible category. Furthermore, the percentage of the results of small-group testing is 76.44% and for field-testing is 82.97%. Thus, the developed product is suitable to be used as a media for physics learning. The web is developed using the Problem-Based Learning (PBL) for the Basic Physics II subject